Olbrzymi brodawczak splotu naczyniówkowego - opis przypadku = Giant choroid plexus papilloma - case report - Kamila Woźniak; Dorota Ratuszek-Sadowska; Agnieszka Nowacka; Maciej Śniegocki (Kazimierz Wielki University, 2016)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Nowacka Agnieszka, Śniegocki Maciej. Olbrzymi brodawczak splotu naczyniówkowego - opis przypadku = Giant choroid plexus papilloma - case report. Journal of Education, Health and Sport. 2016;6(8):688-694. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61144 http://ojs.ukw.edu.pl/index.php/johs/article/view/3797     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016.     Olbrzymi brodawczak splotu naczyniówkowego - opis przypadku   Giant choroid plexus papilloma - case report   Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Agnieszka Nowacka1, Maciej Śniegocki1    1.        Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2.        Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu       Streszczenie   Brodawczak splotu naczyniówkowego (ang. choroid plexus papilloma) to rzadki nowotwór ośrodkowego układu nerwowego, wywodzący się z nabłonka splotu naczyniówkowego układu komorowego mózgowia. W 50% przypadków rozwija się w komorze bocznej, w 40% w komorze IV i w 5% w komorze III. Guzy splotu naczyniówkowego występują przede wszystkim w 1. dekadzie życia. Guz produkuje płyn mózgowo - rdzeniowy, co przyczynia się do wodogłowia i nadciśnienia śródczaszkowego. Histologicznie zbudowany jest ze struktur brodawkowatych, utworzonych przez cylindrycznego kształtu komórki spoczywające na błonie podstawnej. Autorzy przedstawiają opis przypadku klinicznego chorej leczonej operacyjnie w Klinice Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej Szpitala Uniwersyteckiego nr 1 im. dr A. Jurasza w Bydgoszczy z rozpoznanym w badaniu histopatologicznym brodawczakiem splotu naczyniówkowego.   Słowa kluczowe: brodawczak splotu naczyniówkowego, nowotwór, ośrodkowy układ nerwowy, neurochirurgia.   Abstract   Choroid plexus papilloma is a rare cancer of the central nervous system, derived from epithelial cells of the choroid plexus of the ventricular system of the brain. In 50% of cases resolve the side chamber, and in 40% in the fourth chamber and 5% in the third ventricle. Choroid plexus tumors occur primarily in the first decade of life. The tumor produces cerebrospinal fluid, which contributes to hydrocephalus and brain edema. Histologically is built with papillary structures formed by the cylindrical shape of the cells resting on the basilar membrane. The authors present a case of clinical patient operating treated in the Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery, Dr Antoni Jurasz University Hospital No.1 in Bydgoszcz histopathological diagnosed with choroid plexus papilloma.   Key words: choroid plexus papilloma, cancer, central nervous system, neurosurgery.